Smart campus: Designing a digital environment that supports students' psychological well-being - Hammouri, Lama Nael Mansour; Alrosan, Musallam; Hamdon, Hani Mefleh O; Tashtoush, Mohammad A; Altahayneh, Ziad Lutfi; Al-Momani, Abeer Mohammad; Hawari, Anwar Faisal; Malkawi, Saja Hassan; Neyef Al-Saliti, Rawan Abdul Mahdi; Ali Doum, Hamed Mohammed (Research Journal in Advanced Humanities, 2026)
Smart campus technologies have witnessed increasing interest in modern educational environments due to their role in the quality of educational services and the student experience. Psychological well-being is also a key indicator of the quality of university life. This study aims to examine the levels of smart campus technology implementation and psychological well-being among university students and reveal the nature of the relationship between them. It will also explore differences based on demographic variables and identify the extent to which these variables and the dimensions of the smart campus explain psychological well-being using Structural Equation Modeling (SEM). A descriptive correlational approach was applied. A sample of 200 male and female students participated in the study. The study relied on the Smart Campus Scale and the Psychological Well-being Scale. The results show that the level of implementation of smart campus technologies is moderate. The smart security and safety dimension ranked first, while the smart infrastructure dimension ranked last. In contrast, the level of students' psychological well-being is high. The results also show no statistically significant correlation between the smart campus and psychological well-being. Regarding differences, the results of the four-way analysis of variance reveal statistically significant differences in the implementation level of smart campus technologies attributable to gender (favoring females), the level of use of smart systems, and the number of days attended. Nevertheless, no differences are found based on the college. Moreover, no statistically significant differences are found in the level of psychological well-being attributable to any of the demographic variables. The structural equation modeling (SEM) results show that demographic variables explain a limited proportion of the variance in the smart campus dimensions. Gender and college have a significant effect on certain dimensions, while the number of days attended has no significant effect. Regression model results indicate that some smart campus dimensions have varying effects on psychological well-being. The smart safety and security dimension shows a significant positive effect, as does the smart mobility dimension, while the smart learning environment (and sustainability and smart environment) shows a significant negative effect. The remaining dimensions do not show statistically significant effects.